The Zoroastrian manuscripts of the Matenadaran - Andrés-Toledo, Miguel Ángel. (Leiden ; Boston)
viii, 407 sayfa
Keywords: “Armenia was a stronghold of the Zoroastrian religion in antiquity and late antiquity. Of the rich Zoroastrian literature that was composed and transmitted in the region, no single text was extant there after long periods of cultural, political and religious changes. The three Zoroastrian manuscripts of this facsimile edition, containing precious copies of texts in the Avestan, Pahlavi and Zoroastrian New Persian languages, are the only exception. Stemming from Iran and now preserved at the Mesrop Mashtots Institute of Ancient Manuscripts (Matenadaran), they are heirs of an ancient Iranian faith that once flourished also in Armenia“ --